2011
DOI: 10.3399/bjgp11x601334
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal care: development of a psychometric multidimensional satisfaction questionnaire (the WOMBPNSQ) to assess women's views

Abstract: BackgroundPostnatal care is the neglected area of pregnancy care, despite repeated calls to improve it. Changes would require assessment, which should include women's views. No suitable satisfaction questionnaire exists to enable this. AimTo develop a multidimensional psychometric postnatal satisfaction self-completion instrument. SettingTen maternity services in south west England from 2006-2009. MethodSources for questions were literature review, fieldwork, and related published instruments. Principal compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 44 publications
1
23
0
4
Order By: Relevance
“…Different instruments were developed to determine women's satisfaction with labor and childbirth for English-speaking women [10][11][12][13]. These questionnaires assess the woman's satisfaction with childbirth as a multidimensional construct, with each dimension, including various aspects relevant to measuring satisfaction [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different instruments were developed to determine women's satisfaction with labor and childbirth for English-speaking women [10][11][12][13]. These questionnaires assess the woman's satisfaction with childbirth as a multidimensional construct, with each dimension, including various aspects relevant to measuring satisfaction [14].…”
Section: Introductionmentioning
confidence: 99%
“…The Women's Views of Birth Labour Satisfaction Questionnaire (WOMBLSQ) is the oldest and remains a sound instrument that not only assesses the dimensions which are common to most scales but also pain relief dimension that has been suggested as a critical factor for satisfaction [15]. The (WOMBLSQ) [12] and Women's Views of Birth Postnatal Satisfaction Questionnaire (WOMBPNSQ) [13] are multidimensional and sensitive to differences in settings and between women. It has the capacity to reflect the most relevant aspect of maternal satisfaction with care during labor.…”
Section: Introductionmentioning
confidence: 99%
“…It is unclear if clients in other countries have the same importance ratings, experiences and MIDs as Dutch clients. Other self-report instruments in maternity care, such as the Women’s Experience of Maternity Care Questionnaire of the NHS, overall indicate very good experiences ( Peterson et al , 2005 ; Redshaw & Heikkila , 2010 ; Smith , 2001 , 2011 ). Therefore, the MID in other developed countries will probably be in about same magnitude as our MID estimates.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the content of postnatal care services, Smith found that 12 specific dimensions are extremely important and affect women's satisfaction with postnatal care: support from health professionals, a partner, or social support services; care from a general practitioner and health visitor; receiving advice about contraception, feeding the baby, and maternal health; continuity of care; duration of inpatient stay; home visits; and pain after childbirth. In addition, Johansson and others interviewed 21 Swedish‐speaking parents who had given birth to their first child after a normal pregnancy and delivery.…”
Section: Literature Reviewmentioning
confidence: 99%